TINGKAT KETERAMPILAN TEKNIK DASAR BOLA VOLI PADA MASA PANDEMI COVID-19 KLUB BOLA VOLI MUTIARA SERASI UNGARAN TAHUN 2020/2021 - Yusril khirom; Catur Wahyu Priyanto; Miftachul A’la (JURNAL ILMIAH PENJAS (Penelitian, Pendidikan dan Pengajaran), 2022)
This study aims to determine the level of basic volleyball technical skills during the Covid-19 pandemic at Mutiara Serasi Club Ungaran. This study uses a quantitative descriptive approach with a skills test method. The population in this study were athletes from the Mutiara Serasi club. The sampling technique used purposive sampling with a total of 20 male students. data analysis method using percentage description. Service research results get good results 19 athletes with a percentage of 90%, just 2 athletes with a percentage of 10%. Overpassing research got good results 12 athletes with a percentage of 60%, only 6 athletes with a percentage of 30% and 2 athletes with a percentage of 10%. Underpassing research got good results 4 athletes with a percentage of 20%, only 10 athletes with a percentage of 50%, 5 athletes in a percentage of 25% and less than 1 athlete in a percentage of 5%. Smash research got good results 17 athletes in the percentage of 85%, enough 2 athletes in the percentage of 10%, while 1 athlete in the percentage of 5%. Blocking research got good results 19 athletes in the percentage of 95%, just 1 athlete, in the percentage of 5%.